Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 3 - P.S. Problem Solving - Page 308: 10e


See below.

Work Step by Step

The formula: $m=\frac{f(2+h)-4}{h}$ At $h=-1$: $\frac{(2+(-1))^2-4}{-1}=\frac{1-4}{-1}=\frac{-3}{-1}=3$ At $h=1$: $\frac{(2+(1))^2-4}{1}=\frac{9-4}{1}=\frac{5}{1}=5$ At $h=0.1$: $\frac{(2+(0.1))^2-4}{0.1}=\frac{4.41-4}{0.1}=\frac{0.41}{0.1}=4.1$ These values match the ones found in the earlier parts.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.